2022
DOI: 10.1002/acm2.13819
|View full text |Cite
|
Sign up to set email alerts
|

Automated field‐in‐field whole brain radiotherapy planning

Abstract: Purpose We developed and tested an automatic field‐in‐field (FIF) solution for whole‐brain radiotherapy (WBRT) planning that creates a homogeneous dose distribution by minimizing hotspots, resulting in clinically acceptable plans. Methods A configurable auto‐planning algorithm was developed to automatically generate FIF WBRT plans independent of the treatment planning system. Configurable parameters include the definition of hotspots, target volume, maximum number of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In other work, we have shown that automatically adding subfields results in higher levels of acceptability. 26,28,29 Chest wall acceptability results were also lower for use as-is, although high after minor edits. This is consistent with our earlier work, where we showed that these plans are easily corrected to give clinically acceptable plans.…”
Section: Review Resultsmentioning
confidence: 96%
“…In other work, we have shown that automatically adding subfields results in higher levels of acceptability. 26,28,29 Chest wall acceptability results were also lower for use as-is, although high after minor edits. This is consistent with our earlier work, where we showed that these plans are easily corrected to give clinically acceptable plans.…”
Section: Review Resultsmentioning
confidence: 96%
“…Physicians noted that they would prefer to use additional brain sub-fields to reduce the size of the 107% hotspot. While our current CSI approach does not include sub-fields for the brain fields, they could easily be added using a technique that has been separately developed for whole brain radiation ( 15 ). Finally, one physician noted that the MLCs could be opened around the back of the skull to ensure that patients with pseudomeningoceles would be treated properly, with no negative effect on the patient.…”
Section: Discussionmentioning
confidence: 99%
“…To alleviate demanding workflows and increase global access to high-quality radiation therapy, artificial intelligence has been introduced to automate various aspects of the radiation therapy treatment planning process. The Radiation Planning Assistant (RPA) planning team has developed algorithms to automate contouring, treatment planning, and quality assurance for adult disease sites, including the cervix, chest wall, spine, head and neck, and whole brain (10)(11)(12)(13)(14)(15). Court et al recently summarized how the RPA was designed alongside leaders in resource-constrained countries to address the global expertise gap in radiation oncology (16).…”
Section: Introductionmentioning
confidence: 99%